Use of the nicotine skin patch by smokers in 20 communities in the United States, 1992-1993. (1997) - Cummings, K M; Hyland, A; Ockene, J K; Hymowitz, N; Manley, M
Abstract : OBJECTIVE: To measure the characteristics of smokers associated with the use of the nicotine skin patch in the general population and to evaluate whether use of the patch is associated with successful smoking cessation. DESIGN: Data from two surveys conducted in 20 communities in the United States as part of the National Cancer Institute's Community Intervention Trial for Smoking Cessation (COMMIT) study. Nicotine patch prevalence was estimated using data from a 1993 cross-sectional survey of 13691 current and former smokers. The effectiveness of the nicotine skin patch as a smoking cessation aid was evaluated adjusting for other covariants using data from a cohort tracking study of 9809 smokers who were followed between 1988 and 1993. As the nicotine patch was not available to consumers until January 1992, analyses were restricted to respondents who reported themselves to be current smokers in 1993 or former smokers who reported quitting after January 1992. OUTCOME MEASURES: Current and former smokers who reported having made a serious effort to stop smoking in the past five years were asked to indicate whether they had used the nicotine skin patch to help them stop smoking. Those answering "Yes", were classified as nicotine patch users. Smoking cessation was based on self-report. A "quitter" was defined as someone who had been a smoker as of January 1992 who reported in 1993 not smoking any cigarettes for the preceding six months or longer. RESULTS: The prevalence of nicotine patch use by smokers averaged across the 20 study communities was 12.8%, making the patch one of the most popular cessation methods used by smokers. Compared with non-users, patch users were more likely to be female, white, have higher annual household incomes, be more motivated to stop smoking, and to smoke more heavily. Among low-income smokers (annual household income below US10000), nicotine patch use was significantly higher among those who lived in a state where the public insurance programme (Medicaid or Medi-Cal) included the patch as a benefit (12.1% vs 7.7%). Among those who made an attempt to quit smoking, the likelihood of successful quitting was more than twice as high among patch users compared with non-users. Among patch users, the highest quit rates were observed among those who used the patch for between one and three months. CONCLUSIONS: The nicotine skin patch is a popular and effective means of smoking cessation. Use of the nicotine patch, especially by low-income smokers, could be increased by reducing the out-of-pocket expenditure required for smokers to get the product.